A comparison between the flexor hallucis brevis and adductor pollicis muscles in atracurium-induced neuromuscular blockade using acceleromyography: A prospective observational study. Issue 1 (January 2020) - Le Merrer, Maëlle; Frasca, Denis; Dupuis, Maxime; Debaene, Bertrand; Boisson, Matthieu
Abstract : BACKGROUND: Neuromuscular blockade (NMB) monitoring is essential to avoid residual NMB. While the adductor pollicis is the recommended site for monitoring recovery, it is not always accessible. The flexor hallucis brevis could be an interesting alternative. OBJECTIVE: The aim of our study was to compare NMB onset and recovery at both sites. DESIGN: Prospective observational study. SETTING: Operating rooms at the University Hospital of Poitiers, France. PATIENTS: Sixty patients scheduled for surgery under general anaesthesia with neuromuscular blocking agents were enrolled from January 2016 to September 2017. Data from 56 patients were finally analysed. Among these, 11 patients received pharmacological reversal with neostigmine and atropine before emergence from anaesthesia. INTERVENTION: After atracurium injection, NMB onset and recovery at the adductor pollicis and flexor hallucis brevis were monitored simultaneously. MAIN OUTCOME MEASURES: The time to NMB onset, defined as a train-of-four (TOF) count equal to 0, and the times to NMB recovery: TOF = 1, TOF = 4, T4/T1 ratio = 0.75 and T4/T1 ratio more than 0.90. RESULTS: NMB onset was significantly slower at the flexor hallucis brevis with a mean onset time of 4.4 ± 1.5 versus 3.7 ± 1.2 min at adductor pollicis ( P = 0.0001). Recovery to TOF = 1 was significantly slower at flexor hallucis brevis. No difference was found for TOF = 4. The full recovery of NMB (T4/T1 > 0.90) was significantly faster at flexor hallucis brevis with a mean time to recovery of 59.5 ± 9.9 versus 64.5 ± 10.7 min at adductor pollicis ( P < 0.0001), a difference of 4.9 min between both sites. This difference was not present after pharmacological reversal with a mean time to recovery of 53.0 ± 12.2 min at flexor hallucis brevis versus 54.0 ± 12.4 min at adductor pollicis ( P = 0.28). However, NMB onset and recovery did not follow the same pattern in individual patients. CONCLUSION: Flexor hallucis brevis could be an interesting alternative site for NMB monitoring when the adductor pollicis is not accessible. However, in the absence of pharmacological reversal, monitoring at the hallucis brevis muscle should be used with caution for the detection of residual paralysis. TRIAL REGISTRATION: ClinicalTrials.gov (NCT02825121).